Mucorales prevalence and azole-resistance surveillance on different indoor environments: a menace to be tackled - Viegas, Carla (2018)
Aim of the study - Mucorales species can cause severe infections among immunocompromised patients. Mucormycosis is associated with a great deal of morbidity and infections caused by Mucorales species among patients receiving triazole prophylaxis. Considering the clinical relevance of Mucorales order, the prevalence of these fungal species and azole-resistance surveillance should be ensured in fungal exposure assessments. In this study, the prevalence of Mucorales species indoor was determined in different occupational settings and dwellings. Azole-resistant Mucorales were determined by morphological and molecular criteria.